2001
DOI: 10.2500/108854101778250625
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Autoimmunity in Chronic Urticaria

Abstract: A subset of patients with idiopathic chronic urticaria (CU) has been recently classified as autoimmune on the basis of two main findings: association with thyroid autoimmunity and with anti-IgE and/or anti-IgE receptor antibodies. The association of CU with thyroid autoimmunity has been known since 1983, but its frequency varies in different reports. The objective of the present study was to verify the prevalence of thyroid antibodies (anti-thyroid peroxidase, TPO; thyroglobulin, TG; TSH-receptor, TSH-R) in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
4
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 0 publications
6
25
4
6
Order By: Relevance
“…Female predilection was more prominent in chronic urticaria with high anti TPO antibody which was consistent with previous studies. [2][3][4][5][6][7] Severe urticaria was seen in patients with high anti TPO antibody in our study unlike most of the previous studies. 7,16,17 ASST positive patients also had high urticaria activity in our study, in concordance with other reports but unlike other studies where no correlation was found between the severity of urticaria and ASST positivity.…”
Section: Discussioncontrasting
confidence: 56%
“…Female predilection was more prominent in chronic urticaria with high anti TPO antibody which was consistent with previous studies. [2][3][4][5][6][7] Severe urticaria was seen in patients with high anti TPO antibody in our study unlike most of the previous studies. 7,16,17 ASST positive patients also had high urticaria activity in our study, in concordance with other reports but unlike other studies where no correlation was found between the severity of urticaria and ASST positivity.…”
Section: Discussioncontrasting
confidence: 56%
“…A associação entre UC e DAT foi descrita por vários autores, sendo considerada bem estabelecida (7)(8)(9)(10)(11)(12)(13)(14)21). Em nosso trabalho, concordando com poucos relatos, esta associação não ocorreu (16,17).…”
Section: Discussionunclassified
“…Assim, considerando que pelo menos uma parcela dos pacientes com UCI tem, na verdade, uma doença autoimune, seria plausível acreditar que uma associação com DAT realmente exista, visto tratar-se de duas doenças com mecanismos patogênicos semelhantes. No entanto, entre os trabalhos que encontraram uma associação entre DAT e UC, a maioria apresentou dificuldades metodológicas (7)(8)(9)(10)(11). A prevalência de anticorpos anti-tireoidianos em pacientes com UC variou de 11,7% a 28,6%.…”
Section: Discussionunclassified
See 2 more Smart Citations